2022
DOI: 10.3390/coatings12050683
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ti-Al-Si Gradient Coating Based on Silicon Concentration Gradient and Added-Ce

Abstract: Titanium and titanium alloys have excellent physical properties and process properties and are widely used in the aviation industry, but their high-temperature oxidation resistance is poor, and there is a thermal barrier temperature of 600 °C, which limits their application as high-temperature components. The Self-generated Gradient Hot-dipping Infiltration (SGHDI) method is used to prepare the Ti-Al-Si gradient coating based on the silicon concentration with a compact Ti(Al,Si)3 phase layer, which can effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In a similar research, Wang et al [ 33 ] investigated the effects of cerium addition on the self‐generated Ti–Al–Si coating. He showed that for a certain period, only a Ti(Al,Si) 3 phase layer was formed on the surface of the Ti–6Al–4V alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar research, Wang et al [ 33 ] investigated the effects of cerium addition on the self‐generated Ti–Al–Si coating. He showed that for a certain period, only a Ti(Al,Si) 3 phase layer was formed on the surface of the Ti–6Al–4V alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Ti 5 Si 3 phase not only has good stability but also has a pinning effect, which can improve the adhesion of the oxidized coating. [32] In a similar research, Wang et al [33] investigated the effects of cerium addition on the self-generated Ti-Al-Si coating. He showed that for a certain period, only a Ti (Al,Si) 3 phase layer was formed on the surface of the Ti-6Al-4V alloy.…”
Section: Oxidation Resistancementioning
confidence: 99%
“…The reason for the appearance of these three hot-dip aluminum phases is the interdiffusion of the Al and Ti atoms between the composite substrate and TiAl3 coating with the extent of corrosion time. The formation of the transition diffusion layer of TiAl2, TiAl, and Ti3Al can reasonably reduce crack propagation or development, so the crack does not extend to the substrate [51]. 3 are the atomic content ratios corresponding to those indicated in Figure 7b.…”
Section: Cross-sectional Morphologies and Surface Analysis Of The Hot...mentioning
confidence: 99%
“…By adjusting the process parameters, different combinations of ductile TiNi and hard Ti 2 Ni intermetallic phases can be synthesized on the Ti-6Al-4V surface to obtain adjustable surface properties. Hot-dip aluminizing is a mature and extensible process [13,14]. Wang, Z. et al [14] prepared a Ti-Al-Si gradient coating based on silicon concentration gradients and added Ce to modify the coating.…”
Section: Introductionmentioning
confidence: 99%
“…Hot-dip aluminizing is a mature and extensible process [13,14]. Wang, Z. et al [14] prepared a Ti-Al-Si gradient coating based on silicon concentration gradients and added Ce to modify the coating. The coating has a dense Ti(Al,Si) 3 phase layer, which can effectively improve the high-temperature oxidation resistance of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%